ENT530: Bokitta Hijab/ Muhammad Haziq Hazwan Musa ... [et. al] - Musa, Muhammad Haziq Hazwan; Noor Junaidi, Noor Farah Adila; Sabri, Nur Nadirah; Mohamed Tahir, Nurul Hazie Sharmira (2019)
Bokitta Hijab is branch business located at No 29-2, Jalan PJU 5/20E, The Strand, Kota Damansara, 47810, Petaling Jaya, Selangor. This business focus on a bumiputera business to provide the best service to its customers in the field of fashion. Bokitta Hijab is now getting better with the new design and types of fabric for scarf. The owner need to think wisely and give more attentions which is from a small problem to the big one in order to be prepared for the incoming challenge.